Graphene layers‐wrapped Fe/Fe5C2 nanoparticles supported on n‐doped graphene nanosheets for highly efficient oxygen reduction - Hu, Enlai (2020)
Synthesis of highly efficient nonprecious metal electrocatalysts for the oxygen reduction reaction (ORR) superior to platinum (Pt) is still a big challenge. Herein, a new highly active ORR electrocatalyst is reported based on graphene layers-wrapped Fe/Fe5C2 nanoparticles supported on N-doped graphene nanosheets (GL-Fe/Fe5C2/NG) through simply annealing a mixture of bulk graphitic carbon nitride (g-C3N4) and ferrocene. An interesting exfoliation–denitrogen mechanism underlying the conversion of bulk g-C3N4 into N-doped graphene nanosheets is revealed. Owing to the high graphitic degree, optimum N-doping level and sufficient active sites from the graphene layers-wrapped Fe/Fe5C2 nanoparticles, the as-prepared GL-Fe/Fe5C2/NG electrocatalyst obtained at 800 °C exhibits outstanding ORR activity with a 20 mV more positive half-wave potential than the commercial Pt/C catalyst in 0.1 m KOH solution and a comparable onset potential of 0.98 V. This makes GL-Fe/Fe5C2/NG an outstanding electrocatalyst for ORR in alkaline solution.